2012
DOI: 10.1097/ccm.0b013e31822efa14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of selective mineralocorticoid and glucocorticoid agonists in canine septic shock

Abstract: Background Corticosteroid regimens that stimulate both mineralocorticoid and glucocorticoid pathways consistently reverse vasopressor-dependent hypotension in septic shock, but have variable effects on survival. Objective and Methods To determine if exogenous mineralocorticoid and glucocorticoid stimulation have distinct effects, and whether the timing on such stimulation alters their effects, in septic shock. Desoxycorticosterone (DOC), a selective mineralocorticoid agonist; dexamethasone (DEX), a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
5
31
0
1
Order By: Relevance
“…Transfusing 42-day-old washed stored blood lessened the degree of lung and liver injury when compared with unwashed controls, decreased vasopressor requirements (reversed shock), and improved cardiac performance (Figures 2 and 3). 28,29 In contrast, transfusing washed fresher blood had a different and opposite effect that made these same parameters worse when compared with unwashed controls.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Transfusing 42-day-old washed stored blood lessened the degree of lung and liver injury when compared with unwashed controls, decreased vasopressor requirements (reversed shock), and improved cardiac performance (Figures 2 and 3). 28,29 In contrast, transfusing washed fresher blood had a different and opposite effect that made these same parameters worse when compared with unwashed controls.…”
Section: Discussionmentioning
confidence: 92%
“…The LIS in a previously published scoring system increases our ability to find the abnormalities in the lungs, which includes mean pulmonary artery pressure, alveolar-arterial oxygen gradient, plateau pressure, O 2 saturation, and respiratory rate. 1,28,29 (B,D) The LIS is plotted in the same fashion as the shock score for old and fresh blood. In each of these panels, unwashed blood is represented by a solid line and washed blood by a dashed line.…”
Section: Serial Mean Levels Of Plasma Cfh and Haptoglobinmentioning
confidence: 99%
“…However, this test is cumbersome, and its clinical utility during sepsis has not been established (9,20,39). Furthermore, no consensus exists for what random cortisol value defines relative adrenal insufficiency in septic shock or indicates the need for exogenous therapy (3,6,17,20,23,25,(33)(34)(35). This lack of reliable diagnostic criteria has led to skepticism regarding the existence of CIRCI and hampered trials evaluating corticosteroid replacement therapy.…”
mentioning
confidence: 99%
“…In a canine model of severe septic shock due to Staphylococcus aureus pneumonia, we previously demonstrated that desoxycorticosterone pivalate, a selective mineralocorticoid agonist, started 72 h before sepsis (25), or therapeutic dexamethasone, a selective glucocorticoid agonist, given at the onset of sepsis either alone or with desoxycorticosterone (26), reversed shock and improved survival. How-ever, dexamethasone started 48 h before sepsis, and desoxycorticosterone started at the onset of infection, were not beneficial in this S. aureus pneumonia model (25). Thus, the effect of selective corticosteroids on outcomes in this model of septic shock has been previously fully described (25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation